2004
DOI: 10.1534/genetics.104.028738
|View full text |Cite
|
Sign up to set email alerts
|

ospC Diversity in Borrelia burgdorferi

Abstract: The outer surface protein C (ospC) locus of the Lyme disease bacterium, Borrelia burgdorferi, is at least an order of magnitude more variable than other genes in the species. This variation is classified into 22 ospC major groups, 15 of which are found in the northeastern United States. The frequency distributions of ospC within populations suggest that this locus is under balancing selection. In multiple-niche polymorphism, a type of balancing selection, diversity within a population can be maintained when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
273
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(295 citation statements)
references
References 74 publications
18
273
4
Order By: Relevance
“…These and other observations in both North America (18,40,41) and Europe (38,42,43) have led to a hypothesis about the importance of diverting larval ticks away from their major reservoir host species to achieve a lower nymphal infection prevalence. Our results are consistent with that hypothesis: there were direct relationships between mouse density and nymphal infection prevalence and between the population structure of B. burgdorferi, a proxy for evaluating reservoir host contributions (39), and nymphal infection prevalence. Extrapolation to the y intercept beyond the data range of Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These and other observations in both North America (18,40,41) and Europe (38,42,43) have led to a hypothesis about the importance of diverting larval ticks away from their major reservoir host species to achieve a lower nymphal infection prevalence. Our results are consistent with that hypothesis: there were direct relationships between mouse density and nymphal infection prevalence and between the population structure of B. burgdorferi, a proxy for evaluating reservoir host contributions (39), and nymphal infection prevalence. Extrapolation to the y intercept beyond the data range of Fig.…”
Section: Discussionsupporting
confidence: 92%
“…To investigate the differences among sites in vaccine effect, we examined the genotypes of B. burgdorferi strains at a polymorphic locus between their 16S and 23S ribosomal RNA genes (27,32). The rationale was the findings of different population structures among vertebrate taxa for LD Borrelia species in Europe (38) and for B. burgdorferi in New York (39). In other words, the strain structure of B. burgdorferi is an indicator of the relative contributions of mice and other reservoir hosts to infecting larvae (27).…”
Section: Antibody Responses and Infections Of Immunized Micementioning
confidence: 99%
“…This view is supported by the finding of significant host specificity in B. burgdorferi ss, where different ospC genotypes were associated with different mammal species (Brisson & Dykhuizen, 2004). However, in the present study, we found no conclusive evidence for host specificity of ospC genotypes (although the analysis approached statistical significance in one of the regions).…”
Section: Discussionsupporting
confidence: 56%
“…The high intrapopulation diversity at ospC must be maintained by some sort of balancing selection. There is evidence that host species specificity is one important factor (Brisson & Dykhuizen, 2004), but negative frequency-dependent selection mediated by host immunity could also play a role (Dykhuizen & Brisson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the significance of OspC type have reached contradictory conclusions. Some studies have found a correlation between OspC type and wild rodent host specificity [129], but others found no such link [130]. The OspC types of human clinical isolates have also been correlated with invasive and non-invasive phenotypes [128,131].…”
Section: B Burgdorferi Products Required For Mammalian Infectionmentioning
confidence: 99%